Rhythms and cycles in happiness - Wolfgang Maennig; Malte Steenbeck; Markus Wilhelm (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2013)
This study analyses time-dependent rhythms in happiness in three aspects. We show that the Sunday neurosis exists exclusively for men with a medium level of education and both men and women with high levels of education. Men with high levels of education may even experience a weekend neurosis. This study is the first to test for intra-monthly rhythms and to demonstrate that men with a lower educational background may suffer from negative effects on happiness towards the end of the month, potentially due to liquidity problems. The study is also the first to demonstrate that - even when controlling for health and income effects - happiness exhibits seasonal effects over the annual period, depending on gender and education.
Keywords: I31; N70; Q48; 330; happiness; life satisfaction; weekend neurosis; rhythms in time